Institutionalization of Memory in Ukraine in the Conditions of War: Sociological Reflection - Yablonskyi, Yaroslav (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2025)
The article examines the institutionalization of memory in Ukraine during wartime through the case of the Law of Ukraine “On the Fundamentals of the State Policy of National Memory” (2025). The object of analysis is understood not only as a legislative act, but also as a social artifact and a socio-political technology for shaping the national canon, integrating normative, narrative, value-based, and spatial dimensions. The theoretical framework draws on the approaches of M. Halbwachs, J. and A. Assmann, P. Nora, P. Connerton, and J. Olick, which enable an interpretation of the law through the lens of classical concepts of collective memory. The author aims to clarify the sociocultural significance of the law and its role in consolidating collective narratives and norms. Methodologically, the study employs a case study approach based on the analysis of a normative document. Discursive and qualitative document analysis are applied to relate the legal provisions to classical memory theories and to compare the Ukrainian case with the legislation of Poland and Russia. The author argues that the 2025 Law systematizes previous stages in the development of Ukrainian memory policy (decommunization and de-russification processes) and marks a transition from fragmented interventions to the formation of a comprehensive strategy in the field of memory policy. The new framework of memory consolidates a narrative of struggle and resistance, the remembrance of victims of totalitarian regimes, and the values of freedom and dignity, meanwhile providing an institutional definition of “sites of memory” and commemorative practices. The article offers a sociological interpretation of the Law as a case of normative institutionalization of memory in Ukraine, opening prospects for further research in cultural memory studies. The study is conceived as a foundation for the development of state memory strategies and educational and cultural programs aimed at societal consolidation. It also contributes to expanding the role and significance of the sociology of memory in understanding post-Soviet and postcolonial contexts.